PENGARUH PERSEPSI NILAI DAN PERSEPSI RESIKO TERHADAP NIAT BELI KOSMETIK ORGANIK - ARIYANTI, KURNIA (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract: This study aims to analyze and discuss the influence of perceived velue and perceived risk an purchase intentions. This study focuses on an kosmetik organik brand Sariayu.As the first in organis cosmetics in Indonesia. The innovations organic products, gives impact on consumer behavior in assessing the value and risks of the products that can influence consumer purchase intentions. The sampling technique that used was purposive sampling with sample size of 220 respondents. The research instrument used was questionnairs, documentation, interview, and the data obtained were processed using regression analysis. The results showed thet there is significant influence ofperceived velue and perceived risk on purchase intentions. The influence of perceived velue is bigger than the of perceived risk on purchase intentions. Keywords: perceived value, perceived risk, and purchase intentions.